Photocatalytic activity enhancement of g-C3N4/BiOBr in selective transformation of primary amines to imines and its reaction mechanism - Saranya Juntrapirom (2020)
© 2020 Elsevier B.V. Herein, the photocatalytic activity of g-C3N4/BiOBr (CB) heterojunction in the oxidative C–N coupling of benzylamine under atmospheric air using cool white LED light was reported for the first time. The CB heterojunction was prepared by two-step combustion-coprecipitation method. By tuning the weight percentage of g-C3N4, the optimal catalyst containing 10.2 wt% of g-C3N4 provided the highest benzylamine conversion of ca. 94% and the best N-benzylidenebenzylamine yield of ca. 82% within 4 h irradiation. The influences of catalyst amount, substrate concentration, light intensity and reaction temperature on photocatalytic performance were also discussed. The CB catalyst also successfully oxidized N-heterocyclic amines and secondary amines into their corresponding imines which extends the scope and potential use of this catalyst in the syntheses of other C[dbnd]N containing biologically active compounds. The enhanced performance of CB heterojunction was mainly ascribed to improved charge transfer and separation intrinsically derived from the staggered band energy configuration of the CB heterojunction as evidenced from photoelectrochemical, steady-state photoluminescence and time-resolved fluorescence studies. Electron paramagnetic resonance (EPR), Hammett and active species quenching results revealed the O2[rad]–-assisted mechanism with a possible carbocationic intermediate being generated. Under anaerobic condition, the reaction can also proceed probably through carbon-centered radical. Based on UV–vis, XPS and Mott-Schottky results, band energy level diagram and a plausible reaction mechanism at solid-liquid interface were also revealed.